2023
DOI: 10.1021/acs.jpcb.2c08818
|View full text |Cite
|
Sign up to set email alerts
|

Insight to the Local Structure of Mixtures of Imidazolium-Based Ionic Liquids and Molecular Solvents from Molecular Dynamics Simulations and Voronoi Analysis

Abstract: While the physicochemical properties as well as the NMR and vibration spectroscopic data of the mixtures of ionic liquids (ILs) with molecular solvents undergo a drastic change around the IL mole fraction of 0.2, the local structure of the mixtures pertaining to this behavior remains unclear. In this work, the local structure of 12 mixtures of 1-butyl-3-methylimidazolium cation (C 4 mim + ) combined with perfluorinated anions, such as tetrafluoroborate (BF 4 − ), hexafluorophosphate (PF 6 − ), trifluoromethyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…It should be noted that the anion–cation, cation–solvent, and anion–solvent interactions mentioned here refer to the average of a large number of molecules or ions in the IL–solvent systems over the whole concentration range and do not refer to interactions between individual molecules or ions at a specific defined composition. Comparing the values of ( g sc – g ac ) and ( g sa – g ca ) listed in Table , it is interesting to note that they are all positive, i.e., | g sc | < | g ac | and | g sa | < | g ca |, indicating that the anion–cation interactions are larger than the cation–solvent or anion–solvent interactions, which is consistent with the previous results from MD simulations, DFT calculations, and FT-IR spectra. According to the magnitude of the ( g sc – g ac ) and ( g sa – g ca ) values, the studied IL–solvent systems can be classified into two types. The first type of systems is those where the solvents are H 2 O and MeOH, and ( g sc – g ac ) is smaller than ( g sa – g ca ), i.e., | g sc | > | g sa |, indicating that the cation–solvent interaction is greater than the anion–solvent interaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that the anion–cation, cation–solvent, and anion–solvent interactions mentioned here refer to the average of a large number of molecules or ions in the IL–solvent systems over the whole concentration range and do not refer to interactions between individual molecules or ions at a specific defined composition. Comparing the values of ( g sc – g ac ) and ( g sa – g ca ) listed in Table , it is interesting to note that they are all positive, i.e., | g sc | < | g ac | and | g sa | < | g ca |, indicating that the anion–cation interactions are larger than the cation–solvent or anion–solvent interactions, which is consistent with the previous results from MD simulations, DFT calculations, and FT-IR spectra. According to the magnitude of the ( g sc – g ac ) and ( g sa – g ca ) values, the studied IL–solvent systems can be classified into two types. The first type of systems is those where the solvents are H 2 O and MeOH, and ( g sc – g ac ) is smaller than ( g sa – g ca ), i.e., | g sc | > | g sa |, indicating that the cation–solvent interaction is greater than the anion–solvent interaction.…”
Section: Resultsmentioning
confidence: 99%
“…As the amount of polar solvent increases, hydrogen-bonding interactions can be formed between the aromatic hydrogen atoms in [Rmim] + and the polar solvent . Moreover, it should be noted that the strength of the anion–solvent and cation–solvent interactions is modulated by changing the composition of the mixture and the polarity of the solvent. , Hu et al compared bonding energy of the cation–solvent and anion–solvent of [Bmim]­[BF 4 ] in different polar solvents by theoretical calculations, which showed that the bonding energy of the cation–solvent was greater than that of the anion–solvent when the solvents are H 2 O and MeOH, whereas the opposite was the case when the solvents are ACN, AC, and DMSO . Therefore, it is not difficult to understand why the anion–solvent and cation–solvent interactions of the studied IL–solvent systems obtained from Λ m by the new model show a different order with the type of the solvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that a crossover occurs between cation−anion and cation-solvent/ anion-solvent distances, with the mole fraction at which this crossover happens being influenced by the solvent's competition for cation−anion interactions (higher for PC and γ-BL compared to ACN). Furthermore, the analysis of local structure using Voronoi polyhedral as a statistical observable 132 revealed that density fluctuation reaches a maximum at low mole fraction, indicating a looser radial position of mixture components compared to their fluctuation in neat states. Moreover, preliminary results from molecular dynamics simulations of D205 in a BmimBF 4 -ACN mixture also show that the average distance between the dye and ions remains relatively unchanged from the neat IL, but increases significantly for X IL values below 0.2.…”
Section: Discussionmentioning
confidence: 99%